The Role of Service Quality and Service Transparency in Building Public Trust in Public Services: A Literature Study - Susi Sugiyarsih (International Journal of Science Education and Cultural Studies, 2025)
Public trust is a major element in making public service delivery effective and legitimate. Service quality and service transparency have often been identified as key determinants of public trust, but the evidence remains fragmented across different public service contexts. The study seeks to synthesize existing research on the role of service quality and service transparency in building public trust in public services. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Articles were retrieved from Google Scholar, Scopus, ScienceDirect and SpringerLink using pre-defined search keywords. Following the screening and eligibility assessment process, 25 studies published between 2019 and 2025 were included in the review. The results indicate that service quality increases public trust via responsiveness, reliability, accessibility, and professionalism, and service transparency strengthens trust via openness, accountability, and access to information. The review further finds that these two factors are complementary dimensions that shape perceptions of governmental competence and integrity. Based on the literature synthesis, an integrated conceptual framework is proposed to explain the relationship of service quality, service transparency and public trust. This study adds value to the public administration literature through the provision of a comprehensive synthesis of the extant evidence and the identification of avenues for future research on public trust in public services.